تأثير تطبيق إستراتيجية مطابقة بطاقة الفهرس (Index Card Match) لترقية استيعاب المفردات العربية لدى طلاب الفصل الرابع في المدرسة الابتدائية الإسلامية المتكاملة بيت الرحيم باريك بوتويه". - Rahma Yani; Eka Rizal; Fajriani Arsya; Oktarina Yusra (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The problem in this research is that some students feel bored when learning Arabic. Apart from that, students also find it difficult to understand and memorize Arabic vocabulary. And also the learning strategies that teachers use are less attractive for elementary school students. The aim of this research is to explain the application of the index card match strategy in improving understanding of Arabic vocabulary for fourth grade students at SDIT Baiturrahim Parik Putuih. The type of research that researchers used in this research is quantitative research. The samples from this research were fourth grade Ar-Rahman as the experimental class and fourth grade Al-Insyirah as the control class. Sampling was carried out using Probability Sampling. The research instrument uses observation and tests. In analyzing the data the researcher used the T test. After the data was analyzed in SPSS, the results obtained were a sig 2-tailed of 0.045 and the value was smaller than 0.05, because the sig 2-tailed of 0.045 was smaller than 0.05, then Ha was accepted. Therefore, the researcher concluded that the influence of the index card match strategy was obtained in improving the understanding of Arabic vocabulary for fourth grade students at SDIT Baiturrahim Parik Putuih.